"Oh my god! You have become so Americanized": Paradoxes of adaptation and strategic ambiguity among female immigrant faculty. Issue 1 (2nd January 2018) - Chen, Yea-Wen; Lawless, Brandi
ABSTRACT: Guided by De La Garza and Ono's differential adaptation theory, we examine discourses from immigrant women faculty in the U.S. academy. We utilize thematic analysis to analyze interviews with 26 self-identified immigrant faculty members. Our analysis reveals three interrelating themes: negotiating foreign-female body politics, navigating paradoxes of adaptation, and deploying strategic ambiguity. We theorize the notion of "micro/macro-adaptation" describing mundane and cumulative adaptations that cultural "strangers" make, negotiate, and/or are expected to enact, which paradoxically can function to further disorient, alienate, or marginalize them.